Altered NMDA Receptor Function in Primary Cultures of Hippocampal Neurons from Mice Lacking the Homer2 Gene - Smothers, C. Thetford (Synapse, 2015)
N-Methyl-D-Aspartate (NMDA) receptors are inhibited during acute exposure to ethanol and are involved in changes in neuronal plasticity following repeated ethanol exposure. The postsynaptic scaffolding protein Homer2 can regulate the cell surface expression of NMDA receptors in vivo, and mice with a null mutation of the Homer2 gene exhibit an alcohol-avoiding and –intolerant phenotype that is accompanied by a lack of ethanol-induced glutamate sensitization. Thus, Homer2 deletion may perturb the function or acute ethanol sensitivity of the NMDA receptor. In this study, the function and ethanol sensitivity of glutamate receptors in cultured hippocampal neurons from wild-type (WT) and Homer2 knock-out (KO) mice were examined at 7 and 14 days in vitro (DIV) using standard whole-cell voltage-clamp electrophysiology. As compared to wild-type controls, NMDA receptor current density was reduced in cultured hippocampal neurons from Homer2 KO mice at 14 DIV, but not at 7 DIV. There were no genotype-dependent changes in whole-cell capacitance or in currents evoked by kainic acid. The GluN2B-selective antagonist ifenprodil inhibited NMDA-evoked currents to a similar extent in both wild-type and Homer2 KO neurons and inhibition was greater at 7 versus 14 DIV. NMDA receptor currents from both WT and KO mice were inhibited by ethanol (10–100 mM) and the degree of inhibition did not differ as a function of genotype. In conclusion, NMDA receptor function, but not ethanol sensitivity, is reduced in hippocampal neurons lacking the Homer2 gene.